Association of antigen-specific T-cell responses with antigen expression and immunoparalysis in multiple myeloma - Fichtner, Sabrina; Hose, Dirk; Engelhardt, Melanie; Meißner, Tobias; Neuber, Brigitte; Krasniqi, Fatime; Raab, Marc-Steffen; Schönland, Stefan; Ho, Anthony Dick; Goldschmidt, Hartmut; Hundemer, Michael (Clinical cancer research, 2015)
Purpose: Cancer testis antigens (CTA) are immunotherapeutical targets aberrantly expressed on multiple myeloma cells, especially at later stages, when a concomitant immunoparesis hampers vaccination approaches. - Experimental Design: We assessed the expression of the multiple myeloma antigen HM1.24 (reported present in all malignant plasma cells) and the CTAs MAGE-A2/A3 and NY-ESO-1 (aberrantly expressed in a subset of patients with myeloma), in CD138-purified myeloma cells by qRT-PCR (n = 149). In a next step, we analyzed the antigen-specific T-cell responses against these antigens by IFNγ EliSpot assay (n = 145) and granzymeB ELISA (n = 62) in relation to stage (tumor load) and expression of the respective antigen. - Results: HM1.24 is expressed in all plasma-cell samples, whereas CTAs are significantly more frequent in later stages. HM1.24-specific T-cell responses, representing the immunologic status, significantly decreased from healthy donors to advanced disease. For the CTAs, the probability of T-cell responses increased in early and advanced stages compared with healthy donors, paralleling increased probability of expression. In advanced stages, T-cell responses decreased because of immunoparesis. - Conclusion: In conclusion, specific T-cell responses in myeloma are triggered by antigen expression but suppressed by tumor load. Future CTA-based immunotherapeutical approaches might target early plasma-cell diseases to establish prophylactically a specific T-cell response against late-stage antigens in immunocompetent patients. Clin Cancer Res; 21(7); 1712-21. ©2015 AACR.
Gesehen am 08.01.2021